2017
DOI: 10.1177/0363546517732743
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hamstring Tendon Autograft Harvest on the Restoration of Knee Stability in the Setting of Concurrent Anterior Cruciate Ligament and Medial Collateral Ligament Injuries

Abstract: A concurrent ACL and MCL injury is a commonly encountered clinical problem. Knowledge regarding the implications of hamstring autograft harvest techniques on joint kinematics may help guide management decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 17 publications
0
24
1
Order By: Relevance
“…gracilis loading. 12 Although the lack of details about the MCL injuries in the present study aggravates comparison with previous cadaveric studies, this study contradicts such studies, since no indications for inferior outcome after HT harvest were found. This finding might illustrate that laxity determined in cadaveric models may not always be clinically relevant.…”
Section: Discussioncontrasting
confidence: 92%
See 4 more Smart Citations
“…gracilis loading. 12 Although the lack of details about the MCL injuries in the present study aggravates comparison with previous cadaveric studies, this study contradicts such studies, since no indications for inferior outcome after HT harvest were found. This finding might illustrate that laxity determined in cadaveric models may not always be clinically relevant.…”
Section: Discussioncontrasting
confidence: 92%
“…Although this does not exclude the possibility of valgus laxity still being present, it should probably be distinguished from the state of a complete MCL injury, which Herbort et al 11 tested biomechanically and reported that the medial hamstrings were crucial for valgus stability in this setting. In contrast, Kremen et al 12 cut only the superficial MCL to mimic a partial MCL injury and reported that an ACL reconstruction in this setting was still not sufficient to restore valgus rotational stability in the absence of ST and The proportion of patients with exact 95% confidence intervals achieving the 1-year patient acceptable symptom state in the Knee Injury and Osteoarthritis Outcome Score subscales for each study group respectively. No significant differences were found between the groups.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations